Early within‐person weight gain and variability during inpatient treatment for anorexia nervosa: Age‐dependent effects on treatment outcome. (16th March 2022) - Kolar, David R.; Meule, Adrian; Naab, Silke; Voderholzer, Ulrich
Abstract: Objective: Early weight gain during inpatient treatment for anorexia nervosa (AN) is a dynamic process characterised by within‐person variability that may be age‐dependent. We examined whether age moderates the effect of within‐person weight gain and variability on treatment outcome. Method: Within‐person level estimates of N  = 2881 underweight adolescents and adults with AN for daily average weight gain (linear slope) and variability (root mean squared errors) were obtained using random‐effects modelling. Between‐person level regression analyses were calculated to assess effects on weight, eating disorder psychopathology and attaining normal body weight (body mass index [BMI]: 18.5–25 kg/m 2 ). Results: Higher weight gain during first 2 weeks of inpatient treatment predicted higher weight, lower drive for thinness and lower body dissatisfaction at discharge, but not lower bulimic symptoms. Moreover, it predicted a higher probability of discharge weight within normal range. Younger age was associated with stronger effects of early weight gain on weight, drive for thinness and body dissatisfaction at discharge. Weight variability was not associated with any outcome. Conclusions: Age moderated effects of early weight gain on treatment outcomes, with larger effects for younger patients. Weight variability alone did not influence treatment across age and should be of lesser clinical concern during early inpatient treatment. Highlights: Higher weight gain during early inpatient treatment predicted higher weight, lower drive for thinness and lower body dissatisfaction at discharge. Younger age was associated with stronger effects of early weight gain on treatment outcome. Weight variability during early inpatient treatment was not associated with treatment outcome.